2018
DOI: 10.2131/jts.43.113
|View full text |Cite
|
Sign up to set email alerts
|

Carcinogenicity of quinoline by drinking-water administration in rats and mice

Abstract: -The carcinogenicity of quinoline was examined by administrating quinoline in the drinking water to groups of 50 F344/DuCrj rats and 50 Crj: BDF1 mice of each sex. In rats, the doses of quinoline were 0, 200, 400, and 800 ppm for males and 0, 150, 300, and 600 ppm for females. In male rats, administration of quinoline was terminated at week 96 due to high mortality caused by tumors. There were significant increases of hepatocellular adenomas, hepatocellular carcinomas, hepatocellular adenomas and/or carcinomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Identification of mammalian metabolites of quinoline 1 and their role in its mutagenicity and tumorigenicity, has been of interest for more than 40 years (Hollstein et al, 1978;Tada et al, 1980Tada et al, , 1982LaVoie et al, 1983;Agarwal et al, 1986Agarwal et al, , 1990Willems et al, 1992;Saeki et al, 1993;Reigh et al, 1996;Suzuki et al, 2000;Dowers et al, 2004;Hakura et al, 2007;Diaz Duran et al, 2015;Matsumoto et al, 2018). Several quinoline arene oxides, e.g., 20 and 27, were initially postulated as possible liver microsomal metabolites of quinoline 1 (Hollstein et al, 1978;Tada et al, 1980Tada et al, , 1982LaVoie et al, 1983), before 5,6-arene oxide 20 was finally confirmed as a major metabolite (Figure 8) (Agarwal et al, 1986).…”
Section: Chemoenzymatic Synthesis Of Isolated and Potential Arene Oxide Metabolites Of Quinolinementioning
confidence: 99%
See 1 more Smart Citation
“…Identification of mammalian metabolites of quinoline 1 and their role in its mutagenicity and tumorigenicity, has been of interest for more than 40 years (Hollstein et al, 1978;Tada et al, 1980Tada et al, , 1982LaVoie et al, 1983;Agarwal et al, 1986Agarwal et al, , 1990Willems et al, 1992;Saeki et al, 1993;Reigh et al, 1996;Suzuki et al, 2000;Dowers et al, 2004;Hakura et al, 2007;Diaz Duran et al, 2015;Matsumoto et al, 2018). Several quinoline arene oxides, e.g., 20 and 27, were initially postulated as possible liver microsomal metabolites of quinoline 1 (Hollstein et al, 1978;Tada et al, 1980Tada et al, , 1982LaVoie et al, 1983), before 5,6-arene oxide 20 was finally confirmed as a major metabolite (Figure 8) (Agarwal et al, 1986).…”
Section: Chemoenzymatic Synthesis Of Isolated and Potential Arene Oxide Metabolites Of Quinolinementioning
confidence: 99%
“…Quinoline 1 is a mammalian hepatocarcinogen and a bacterial mutagen, with its metabolites binding covalently to DNA. Possible pathways responsible for these biological effects continue to be of interest (Hollstein et al, 1978;Tada et al, 1980Tada et al, , 1982LaVoie et al, 1983;Agarwal et al, 1986Agarwal et al, , 1990Willems et al, 1992;Saeki et al, 1993;Reigh et al, 1996;Suzuki et al, 2000;Dowers et al, 2004;Hakura et al, 2007;Diaz Duran et al, 2015;Matsumoto et al, 2018). Cytochrome P-450 (CYP-450) monooxygenases have been identified as responsible for catalyzing epoxidation and dearomatization of quinolines, during mammalian liver metabolism.…”
Section: Introductionmentioning
confidence: 99%